Analisis Peran Dinas Tenaga Kerja dan Transmigrasi Kabupaten Bengkalis dalam Penempatan Tenaga Kerja Lokal di Duri - Zacky Maulana, M; Museliza, Virna; Nurani, Ratna (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to analyze the role of the Bengkalis Regency Manpower and Transmigration Office in the placement of local workers in Duri, focusing on policy effectiveness, implementation of training programs, and efforts to increase local employment. The theory used in this research is the theory of employment policy according to Payaman Simanjuntak Priyono 2018, which includes three indicators: Labor Qualification Suitability, Local Labor Participation and Labor and Company Satisfaction. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The research informants consisted of officials from the Bengkalis Regency Manpower and Transmigration Office, company staff in the Duri area, and local workers who had participated in the job placement program. The results showed that the Manpower and Transmigration Office has run various training programs and cooperation with local companies, but there are still obstacles such as limited employment opportunities, lack of local workforce skills, and not optimal implementation of the workforce placement policy. This research suggests that the Manpower and Transmigration Office should improve synergies with the private sector, expand training programs based on industry needs, and strengthen monitoring and evaluation of the implementation of local worker placement policies in order to improve the competitiveness and welfare of local communities.